Liquidity Analysis Before and During the Covid-19 Pandemic - Hendiarto, R. Susanto; Fauzan, Rafli (Jurnal Ekonomi, 2024)
This study aims to explore the liquidity trends of banking companies with case study of PT Bank Mandiri Tbk, before and during COVID-19 pandemic. This study discusses three proxies, namely: Cash Ratio, Quick Ratio and Current Ratio. The techniques used in this research are verification and descriptive with a quantitative approach, so the research techniques used an explanatory survey methods and descriptive survey methods. In this research, as an object with the population framework. The type of data used is secondary data and collected techniques used a library research (library research) and field research (field research). By using SPSS statistical program, where the results showed that Cash Ratio, Quick Ratio and Current Ratio still increased before the COVID-19 pandemic and decreased during the COVID-19 pandemic. Based on this research, the company used as a case study is still limited on banking company of PT Bank Mandiri Tbk which is listed on Indonesia Stock Exchange. So further research must be carried out using a different research sample with a longer observation period, so it is hoped that the results obtained can be generalized.